PENGEMBANGAN MODUL PEMBELAJARAN KIMIA UNTUK KECAKAPAN MEMBANGUN DAN MENGGUNAKAN KONSEP REDOKS DAN HIDROKARBON KELAS X SMAN 3 SUNGAI KAKAP - Rachmatia, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to answer four main objectives, namely: (1) the design of the module following the stage of (a) purpose and use of chemistry module, (b) target to achieve the learning objectives of chemistry subject of redox and hydrocarbon, (c) reflection can be seen from cognitive score and questionnare responses provided to the learner. (2) stages of learning scenarios: preparation, conditioning the learners, introduction, individual work, assessment of the learner work, reflection and closing as well as assessment. (3) profile of chemistry learning module which consists of the cover, preface, able of contents, the standard of competence (SK), basic competence (KD), indicators, instructions for using the module, a map of the position of the module,  concept map material, descriptions, prerequisites, the final objectives, prior knowlege checking, learning activities (consisting of material description, summary, assignments, and tests formative), evaluation, conclusion, references. (4) acquisition of the concept of redox and hydrocarbons can also be seen from the provision of the questions that serve to test extent to which learners can understand what has been obtained by the learners with the acquisition of early learners ability scores an average of 53,2 and the final ability with an average score of 79. In terms of process, the chemistry learning module could deliver positive results for learners. Keywords: Redox Concept, Hydrocarbon Concept, Learning Module